Positioning and branding tourism destinations for global competitiveness - Rahmat Hashim 1959-; Mohd Hafiz Hanafiah; Mohd Raziff Jamaluddin 1980- (Business Science Reference, 2019)
"This book focuses on the value of destination branding and content marketing in tourism for sustainable growth and competitive advantage. It is a blend of balance theory and practical content, providing a thorough explication of the tools and techniques of branding and marketing for travel, tourism and hospitality industry"...Provided by publisher